Application of BIM Collaborative Design Technology in Intelligent Buildings for Prefabricated Steel Structures - Wang, Heng; Zhu, Wei; Du, Yansheng; Zhang, Wenling; Zhou, Hao; Wang, Rui; Li, Wenhao; Zhang, Pengfei; Huang, Xiaokang; Cao, Zhiliang; Bao, Bingkai (Procedia computer science, 2024)
In recent years, the development of prefabricated buildings has been significantly promoted by China's policy initiatives focusing on innovation, green development, and industrialization in the construction sector. This paper explores the application of Building Information Modeling (BIM) collaborative design technology in the construction of intelligent buildings with prefabricated steel structures. Using the Zhangjiawo Sports Park Project as a case study, we detail the integration of digital design, industrial production, and intelligent construction methodologies. The project leverages BIM for precise modeling (LOD400), optimizing construction through collision analysis, and enhancing natural lighting and ventilation via simulation tools. The prefabrication process employs advanced steel structure manufacturing techniques and intelligent logistics, while on-site construction utilizes automated systems, such as ALC wall panel installation robots. These innovations not only improve construction efficiency and safety but also align with national low-carbon and sustainable development goals. The findings provide valuable insights into the benefits and implementation strategies of BIM and intelligent construction technologies in prefabricated building projects.